Social capital and entrepreneurial intention: Empirical evidence from rural community of Pakistan - Amjad Ali; Sania Yousuf (Journal of Global Entrepreneurship Research, 2019)
Understanding the antecedents of the entrepreneurial intentions is vital in development of entrepreneurship in a region. Entrepreneurship is considered as one of the important elements of local economic development which can be used to address the issues of poverty and scarcity of livelihood opportunities in rural areas of the world. This study investigates the influence of social capital on entrepreneurial intentions in rural area of Pakistan. For this purpose, a representative sample of 325 respondents has been selected from rural community in Gilgit-Baltistan. The constructed model has been estimated using the partial least square method and the results show that social capital has significant positive impact on entrepreneurial intentions by forming perceived desirability, perceived self-efficacy, and perceived social norms towards entrepreneurship. This study recommends rural community of Pakistan should be given awareness about the potential of entrepreneurship opportunities and such awareness programs have unique advantages to various segments of rural community. Women, unemployed individuals, and younger generations in particular may get the maximum benefits as people in mountainous regions have already limited earning options. In such a case, developing entrepreneurial intentions of the mountain community in Gilgit-Baltistan leads to understandings of benefits of initiating their own ventures, get economic advantages, and contribute to households' income.
Keywords: 650; Rural community; Local economic development; Entrepreneurial behavior